De novo thrombotic microangiopathy in two kidney transplant recipients from the same deceased donor: A case series. Issue 7 (27th May 2020) - Roberts, Daniel; Siegman, Ingrid; Andeen, Nicole; Woodland, David; Deloughery, Thomas; Rueda, Jose; Olyaei, Ali; Rehman, Shehzad; Norman, Doug; Lockridge, Joe
Abstract: Thrombotic microangiopathy (TMA) is a recognized and serious complication of renal transplantation. Atypical hemolytic uremic syndrome (aHUS), a subset of TMA, occurs in the setting of dysregulation of the alternative complement pathway and can cause disease in native kidneys as well as recurrence in allografts. De novo TMA represents a classification of TMA post‐transplant in the absence of clinical or histopathological evidence of TMA or aHUS in the native kidney. De novo TMA is a more heterogeneous syndrome than aHUS and the pathogenesis and risk factors for de novo TMA are poorly understood. The association between calcineurin inhibitors (CNI) and de novo TMA is controversial. Anti‐complement blockade therapy with eculizumab is effective in some cases, but more studies are needed to identify appropriate candidates for therapy. We present two cases of de novo TMA occurring immediately in recipients from the same deceased donor and provoking the question of whether deceased donor‐related factors could represent risks for developing de novo TMA.